Building customer delight with AgroBank Batu Pahat through better service quality / Norliana Waris - Waris, Norliana (Faculty of Business and Management, 2011)
The purpose of this research is to build customer delight with AgroBank Batu Pahat through better service quality. ‘Seeking customer satisfaction beyond excellence’ is one of the AgroBank vission. It shows AgroBank commitment to achieve customer delight. But there were still a lot of customers make complaint about services being provided by the bank. ASERVQUAL model developed by Parasuraman (tangibles, reliability, responsiveness, competence and courtesy) was been a main tool in measuring the service quality in AgroBank Batu Pahat. The objectives of this research are to identify the level of customer delight, to describe the customer perception of service quality, to identify the most significance factor that contributes to customer delight based on service quality, and to suggest the strategies that might help AgroBank Batu Pahat in increasing the level of customer delight. The research is conducted by using sampling method. 50 questionnaires have been distributed to the customers in AgroBank Batu Pahat. The findings show that the customers are agreed that AgroBank Batu Pahat provides good service quality. They might be satisfied, but AgroBank still are not able to delight its customers. The bank should continuously improve its service quality in order to gain customer delight and thus being competitive enough in today’s heavy competitive market.